Auxiliary focus - Larry M. Hyman (LibraryPress@UF, 1984)
This paper examines the different properties of what we have termed "auxiliary focus": the interaction between focus and the semantic features of tense. aspect, mood. and polarity. We argue that auxiliary focus has every property of its counterpart (termed "constituent focus") and that in order to account for focus of any type. we shall have to address the following four parameters: (a) realization of focus (prosodic, morphological. syntactic). (b) type of focus (assertive vs. contrastive). (c) scope of focus (subject. object, verb, auxiliary, etc.), and (d) control of focus (pragmatic or grammatical). A particularly interesting side of auxiliary focus is found under point Cd): while in some cases. in some languages, speakers are free to choose [+focus] or [-focus] auxiliarv markers according to the context (pragmatic control), in other cases the choice is dictated by the language itself (grammatical control). We will show that some semantic features of the auxiliary are inherently focused on universal grounds, providing a typology of focus marking on the auxiliary. The relevance of the above considerations of auxiliary focus to the development of tense/aspect systems provides the conclusion to this work.